Prevalence of BRAF, NRAS and c-KIT mutations in Slovenian patients with advanced melanoma - Ebert Moltara, Maja (Radiology and oncology (Ljubljana), 2018)
BRAF, NRAS and c-KIT mutations are characteristics of tumour tissues that influence on treatment decisions in metastatic melanoma patients. Mutation frequency and their correlation with histological characteristics in Slovenian population have not been investigated yet. Patients and methods. In our retrospective analysis we analysed mutational status of BRAF, NRAS and c-KIT in 230 pathological samples of patients who were intended to be treated with systemic therapy due to metastatic disease at the Institute of Oncology Ljubljana between 2013 and 2016. We collected also histological characteristics of primary tumours and clinical data of patients and correlated them with mutational status of tumour samples. Results. The study population consisted of 230 patients with a mean age 59 years (range 25%85). 141 (61.3%) were males and 89 (38.7%) females. BRAF mutations were identified in 129 (56.1%), NRAS in 31 (13.5%) and c-KIT in 3 (1.3%) tissue samples. Among the 129 patients with BRAF mutations, 114 (88.4%) patients had V600E mutation and 15 (11.6%) had V600K mutation. Patients with BRAF mutations tended to be younger at diagnosis (52 vs. 59 years, p < 0.05), patients with NRAS mutations older (61 vs. 55 years, p < 0.05). Number of c-KIT mutations were too low for any statistical correlation, but there was one out of 3 melanoma located in mucus membranes. Conclusions. The analysis detected high rate of BRAF mutations, low NRAS mutations and low c-KIT mutations compared to previously published studies in Europe and North America. One of the main reasons for this observation is specific characteristics of study population.
Keywords: genske mutacije; melanom; metastatski rak; zdravljenje